(untitled) - Leonard G Feather (New York, 1960)
The book covers more than 2000 biographies and 200 photos, it spans the history of jazz from its origins to 1959. The book also features essays on the jazz tradition, its major players and composers, the relationship between jazz and classical music, a social history of jazz in America, the jazzman as critic, and a grammar of jazz language that can serve as an ideal introduction for young listeners. In addition, the book provides a chronology, list of international critic polls, musicians' birthdays and birthplaces, a bibliography, and a discography of recommended recordings
Keywords: jazz music - bio-bibliography,jazz music - discography,jazz musicians - bibliography